(untitled) (Международный научный журнал «Инженер», 2026)
The article examines an approach to the comprehensive assessment of occupational injury risks in the underground mining operations of the Donskoy Mining and Processing Plant using the Kinney method. The analysis is based on data from 180 registered accidents that occurred over a 21-year period at the “Molodezhnaya,” “DNK,” and “ShSC” mines. Hazard identification was carried out using an internal classifier, highlighting the most significant events, including rock falls and collapses, the impact of moving machinery, and falls from heights. Calculations using the Kinney method showed that the risk level for the main hazard type (code 15) exceeds acceptable thresholds (R = 300, with a permissible limit of 70 points), classifying it as an unacceptable risk. Reasoned conclusions were made regarding the necessity of implementing preventive measures based on quantitative analysis. The proposed approach allows for the systematization of industrial safety management at facilities with a high level of injury risk.